Second Phase‐Induced Degradation of Fused MgO Partially Stabilized Zirconia Aggregates1. Issue 4 (20th January 2015) - Quadling, Amanda; Vandeperre, Luc; Parkes, Maria; Lee, William E.; Faber, K.
<x xml:space="preserve">Abstract</x> Magnesia‐partially stabilized zirconia (Mg‐PSZ) fired refractory crucibles used under vacuum induction melting (VIM) furnaces, are routinely cycled above 1500°C in service, sometimes experiencing failure in under a dozen cycles. This has negative financial implications, given the high value Ni–Co superalloys melted in them. To evaluate aggregate response to cycling, the microstructural evolution of two commercial varieties of fused Mg‐PSZ aggregate has been studied within their host refractories, over eight cycles to 1700°C. The aggregates contain 0.1–0.2 wt% alumina and silica impurities and at 1700°C, these generate a liquid phase which on cooling, crystallizes segregated secondary phases of spinel, forsterite, and cordierite. These minerals have thermal expansion coefficients that are markedly different to zirconia and the mismatch in volume change rates between adjacent phases leads to aggregate breakdown. Micro‐Raman mapping reveals internal boundaries within the aggregates which are attributed to retention of original surface concentrations of alumina and silica on zircon sand particles at the time of conversion into zirconia and which act as the main location for secondary phase development. Crucibles made with aggregates containing higher concentrations of stabilizer (>2 wt% MgO) and MgO fines in their matrix phase, show significantly greater aggregate breakdown.